PRACTICAL USE OF DIGITAL SERVICES IN THE EDUCATIONAL PROCESS OF HIGHER PEDAGOGICAL EDUCATION INSTITUTIONS AS A PEDAGOGICAL PROBLEM - Sobchenko, Tatiana; Zhelizniak, Olha (Socio-economic relations in the digital society, 2023)
The article raises the topical issue of the practical use of digital services in the educational process of higher pedagogical educational institutions. The relevance of the presented research is due to scientific and technological progress, the digitalisation of all spheres of life of modern information and digital society. Global changes in the field of higher education, in particular in the current realities of martial law in Ukraine, necessitate the modernisation of higher education on the basis of the use of modern computer technologies, information and digital services. The essence of the concepts of "digitalisation of education" and "digital transformation of education and science" is revealed. It is found that the sphere of informatisation and digitalisation is determined by the legal framework of Ukraine, which regulates and controls its implementation. A number of factors that influence the development of digital services in Ukraine and the possibility of their use in the educational process of pedagogical universities are outlined. The advantages of the practical application of digital services in the organisation of the educational process of higher pedagogical education institutions are analysed. The practical application of digital services for the organisation of asynchronous learning is considered. The ways to improve information and digital competence for all participants in the educational process are outlined. Prospects for further research are outlined.